2016
DOI: 10.1037/men0000025
|View full text |Cite
|
Sign up to set email alerts
|

“If you don’t take a stand for your life, who will help you?”: Men’s engagement in HIV care in Kwazulu-Natal, South Africa.

Abstract: The needs of South African men with HIV may often be overlooked in the provision of HIV services, leading to care programs that do not adequately serve the unique needs of male patients. Additionally, norms of masculinity guide men’s behaviors as they navigate health decision-making and the healthcare systems. The aim of this study is to examine how masculinity influences healthcare access and utilization in South Africa, and to identify opportunities for interventions. The qualitative study took place at one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 29 publications
1
48
0
Order By: Relevance
“…In addition, men feared HIV testing revealing their infidelity in Lesotho [29], Ugandan mining communities [30, 31], rural Zimbabwe [37], and rural South Africa [33]—fearing subsequent abandonment and losing their masculine role as husband. Studies from Malawi, South Africa, Uganda, and Zimbabwe reported younger, single men similarly feared their potential for future marriage would be comprised by testing positive for HIV, resulting in men avoiding HIV testing altogether [32, 3437]. In two studies with men living with HIV in Malawi and South Africa, men expressed concern that as a consequence of not being able to find or keep a spouse, they would also lose the opportunity to become a father, which influenced them to delay HIV testing [34, 35].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, men feared HIV testing revealing their infidelity in Lesotho [29], Ugandan mining communities [30, 31], rural Zimbabwe [37], and rural South Africa [33]—fearing subsequent abandonment and losing their masculine role as husband. Studies from Malawi, South Africa, Uganda, and Zimbabwe reported younger, single men similarly feared their potential for future marriage would be comprised by testing positive for HIV, resulting in men avoiding HIV testing altogether [32, 3437]. In two studies with men living with HIV in Malawi and South Africa, men expressed concern that as a consequence of not being able to find or keep a spouse, they would also lose the opportunity to become a father, which influenced them to delay HIV testing [34, 35].…”
Section: Resultsmentioning
confidence: 99%
“…Men’s belief that the clinic was a place for women was found to contribute to a reluctance to seek an HIV test in four studies [29, 34, 36, 40]. Studies comparing men and women’s experience in accessing testing in South Africa and Lesotho attributed this perception in part to women’s greater opportunity for contact with health and HIV services, particularly their increased access to HIV testing through antenatal care [29, 40].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations